Character Building Through Tahfizul Qur'an: Assessing the Impact on Students at an Islamic High School Palu - Muh Jabir; Nabilah Safitri; Nursyam Nursyam (AL-ISHLAH: Jurnal Pendidikan, 2024)
An important issue facing the Indonesian nation today is a moral crisis. Educational institutions, which are expected to be at the forefront of shaping student character, have not been effectively fulfilling this role. This study aims to assess the character building in Al-Azhar Mandiri High School Palu through the Tahfizul Qur'an program and its implications. This research employs a qualitative approach with a descriptive methodology. Data sources include primary data, collected from the principal, tahfidz teachers, and Al-Azhar Mandiri High School Palu students, and secondary data, obtained through relevant literature. The data analysis technique used is qualitative data analysis with an interactive model. The results indicate that the Tahfizul Qur'an learning at Al-Azhar Mandiri High School Palu is conducted through activities such as muroja'ah (review), tilawati (recitation), verse connection, and memorization deposits. Several factors hinder the tahfidz activities, including unachieved memorization targets, lack of motivation to participate in tahfizul Qur'an learning, quick forgetfulness of memorized verses, and insufficient parental support and motivation. The tahfidz program at Al-Azhar Mandiri High School Palu has significant implications for the formation of religious character and responsibility among students. However, challenges such as motivation and parental support need to be addressed to enhance the program's effectiveness. The study concludes that while the Tahfizul Qur'an program at Al-Azhar Mandiri High School Palu positively impacts student character development, notable challenges must be overcome to optimize its benefits.